ANALISIS BUTIR SOAL UJIAN SEKOLAH BERSTANDAR NASIONAL MATA PELAJARAN MATEMATIKA BERDASARKAN LEVEL BERPIKIR SISWA SD/MI KOTA BENGKULU TAHUN PELAJARAN 2020/2021 - Marya Azpa; Victoria Karjiyati; Irfan Supriatna (Universitas Bengkulu, 2021)
This research intentionally aimed to describe the thinking level of questions of National Standard School Examination (USBN) in Mathematics for SD/MI students in Bengkulu City in 2020/2021 school year. This research was designed in qualitative form with descriptive method. The subjects of the research were the sixth grade elementary students in Bengkulu City. The object of the research was distribution of question categories (thinking levels) in terms of LOTS, MOTS, and HOTS in USBN items for Mathematics at SDN 19 Bengkulu City in 2020/2021 school year. The research instrument applied was documentation of question form of USBN items for Mathematics at SDN 19 Bengkulu City in 2020/2021 school year. In this study, the data were analyzed using categories of thinking levels in terms of LOTS, MOTS, and HOTS; then calculated percentages of the occurrences. To analyze of the questions, the study used the calculation of the percentage (%) of indicators from each question criterion = Numbers of LOTS/MOTS/HOTS items : Total numbers of Mathematics student competensi items x 100%. The findings evidently revealed that there were three percentages of cognitive level: level 1 (level of remembering and understanding) was by 16.67%, level 2 (level of applying) was by 43.33%, level 3 (level of analyzing, evaluating, and creating) was by 40%. In view of this, it could be seen that the school exam questions for Mathematics subject of elementary students in Bengkulu City in the 2020/2021 school year were at the MOTS (Middle Order Thinking Skills) thinking level. Furthermore, based on the results of analysis of the thinking level, it had distributions which were not up to standard yet.Keywords: Question Items, Thinking Level, Mathematics